(untitled) (Fiep Bulletin - online, 2012)
Suicide is a deliberate act, started and conducted by a person with knowledge or expectation of a fatal result. Objective: to understand the perception of nursing professionals that work in urgency and emergency in relation to the patient who attempts suicide. Methods: it is an exploratory-descriptive study, prospective, with quantitative approach, using secondary data of study: Emergency care to patients with suicide attempts in the perception of nursing professionals from Alto Sertão micro-region. The population was composed by all the nursing professionals that work in the department, and 15 nursing professionals participated of the study. The data were collected from November to December 2010, by means of a questionnaire with objective and subjective questions. They were analyzed from a built database using the SPSS software, version 17.0, and it presented the absolute frequency. The data about the perception of nursing professionals were analyzed by a set of techniques of content analysis, as Bardin (2004). The project was analyzed and approved by the Ethics Research Committee of the Integrated College of Patos, as in Opinion n. 0823/2010. Results and discussions: the sample is predominantly constituted by the female sex (60%), in the age group between 26 and 30 years. The bigger demand of the Health Service with suicide attempts are teenagers and young adults (54%), with more incidence of the female sex and in the age group between 15 and 24 years. The suicide attempts refer to a diversity of causes: poisoning (40%) and medicines or chemical agents (33%), followed by hanging (13%), weapon (7%) and firearm (7%). Conclusions: Need for investment in public policies which fulfill the privations in the emergency and mental health departments.